Predictors and histopathological characteristics of non‐diabetic renal disorders in diabetes: a look from the tubulointerstitial point of view. Issue 12 (5th December 2019) - Heybeli, Cihan; Oktan, Mehmet A.; Arda, Hayri U.; Yildiz, Serkan; Unlu, Mehtat; Demir, Tevfik; Cavdar, Caner; Sifil, Aykut; Celik, Ali; Sarioglu, Sulen; Camsari, Taner
Abstract: Background: Prevalence and characteristics of non‐diabetic renal diseases (NDRD) in patients with type 2 diabetes mellitus is different between populations, and seems to be largely dependent on biopsy policies. Aim: To investigate clinical clues for NDRD in patients with type 2 diabetes mellitus and to analyse renal prognosis of patients based on pathological diagnosis. Methods: We retrospectively searched medical records of 115 patients with type 2 diabetes who underwent a renal biopsy between 2004 and 2018. Patients were divided into three groups as diabetic nephropathy (DN), NDRD + DN or NDRD based on histopathological examination. Results: Thirty‐six (31.3%) patients had DN, 33 (28.7%) had DN + NDRD and 46 (40%) had NDRD. The absence of diabetic retinopathy, recent onset of diabetes, abnormal disease chronology, and blood haemoglobin was associated with the presence of NDRD in univariate analysis. Abnormal disease chronology which was defined as the presence of acute proteinuria and/or acute kidney injury that are unexpected to be related to evolution of diabetic nepropathy (odds ratio 4.65, 95% confidence interval 1.44–15.00; P = 0.010) and absence of diabetic retinopathy (odds ratio 3.44, 95% confidence interval 1.32–8.98; P = 0.012) were independently associated with the presence of NDRD in multivariate analysis. Focal segmental glomerulosclerosis was the most frequent type of NDRD. Diseases that affect tubulointerstitial area were more prevalent in the DN + NDRD group compared to the NDRD group ( P = 0.001). Renal survival, which was defined as evolution to end‐stage renal disease, was 59.5 ± 14.4 months, 93.7 ± 11.7 months and 87.2 ± 2.6 months for DN, DN + NDRD and NDRD groups, respectively ( P = 0.005). Conclusions: Renal biopsy is essential in certain clinical conditions as diagnosis of NDRD is vital for favourable renal survival. DN may facilitate superimposed tubular injury in the presence of toxic insults.